An evaluation of some H-T-P technique scores in differential diagnostics - Ambrazevičius, R.; Andrijauskienė, L.; Gailiūnaitė, S.; Gulbinaitė, N.; Ridikas, M. (Psichologija, 1982)
The present paper is concerned with the problem of the H-T-P test quantitative scoring. It gives an account of quantitative drawings scoring of 46 schizophrenic, 25 organic and 30 neurotic cases. The drawings were scored using the J. N. Buck scoring system. The significant difference between good score IQ and flaw score IQ was found only in the group of schizophrenic patients. The experimental data shows the relevance of the H-T-P quantitative scoring for the differential diagnostics of the mental diseases.